Real-time Waveform Monitor System Applying in DCU Based on TCP - CHEN Junbo; DAI Jisheng; LUO Lingbo; LI Cheng; LI Yi (Kongzhi Yu Xinxi Jishu)
It described the design concept and elements of the real-time waveform monitor system used in drive control uint(DCU) of rail transit. According to the requirments of the practical application, TCP is used by the system to display and save all the status information and control information during DCU running, which can help people to take debugging and save time.